(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
This thesis presents a wide-angle X-ray diffraction analysis of thermally induced structural changes in phosphorus-doped n-type silicon monocrystals. The main purpose of the study is to evaluate the influence of high-temperature annealing on the diffraction behavior of the silicon matrix, with particular attention to the dominant (111)Si reflection. The XRD patterns of the initial n-Si sample and the sample annealed at 1300 °C show that the monocrystalline orientation of silicon is preserved after thermal treatment. However, noticeable changes are observed in the intensity, position, and shape of the (111)Si diffraction peak. The initial sample demonstrates a sharp and intense (111)Si reflection, indicating a highly ordered crystalline structure. After annealing, the intensity of the main reflection decreases, while the peak position slightly shifts and the full width at half maximum changes from 0.144° to 0.134°. These variations indicate that high-temperature treatment causes structural reorganization in the silicon lattice, including impurity redistribution, partial relaxation of internal stresses, and modification of defect-related microstrain. The wide-angle XRD representation confirms that the main structural response remains associated with the silicon matrix rather than the formation of strong secondary crystalline phases.